Evaluation of Enterprises’ Bankruptcy Threat - Bivainis, Juozas; Garškaitė, Kristina (Ekonomika, 2000)
Evaluation of enterprises’ bankruptcy threat is a means to evaluate the enterprises’ condition by quantitative parameters and establish the negative tendencies of the enterprises’ activity and the probability of bankruptcy. In the same way, based on the evaluation of enterprises’ bankruptcy threat. it is possible to propose effective strategic decisions on how the enterprise may get out of its difficult condition and avoid bankruptcy or reduce the threat of bankruptcy.Foreign scientists have tried to solve this problem for a lung time. Many foreign scientists have established models, created from certain financial ratios, for evaluation of enterprises’ bankruptcy threat. The American economist, E.I. Altman, has studied this area very extensively. He has created models fur two, five and seven financial ratios.Foreign countries do not use just financial ratios models. Many auditing and other activity companies, engaged in analytical reviews, prognosis and consultation, use not only financial but also non-financial ratios systems to evaluate the condition of enterprises. The English scientist, J. Argenti, has prepared such a different means of evaluation of enterprises’ bankruptcy threat. This method is based on both financial and non-financial ratios.Several financial and non-financial ratios models adapted for evaluation of enterprises’ bankruptcy threat in foreign countries were examined. This analysis, identified that when an enterprise selects any model for evaluation of bankruptcy threat, its reliability depends on the enterprise’s ability to gather and accumulate information about its own activities as well as to analyse and use this information effectively and in time. Direct application of these models to forecast the bankruptcy threat of Lithuanian enterprises would nut he effective, but to adapt it could be expedient.In Lithuania they arc trying to solve the problem of evaluating of enterprises’ bankruptcy threat (financial condition), i.e. to create systems for those financial ratios corresponding to the evaluation of the condition of the enterprises. In financial ratios systems, the activities and specific character of the institutions using them determine the selection of calculable ratios. However, the possibilities of those studies, connected with the evaluation of the condition of enterprises, are increasing. In analysing the condition of enterprises, describing the results of the analysis, and accumulating statistical data, the ratios systems, which arc used to evaluate the condition of enterprises, are being improved and new models are being sought.